Fuzzy Tsukamoto Implementation on Internet of Things to Control Flooding - Riansyah, Andi; Kurniadi, Dedy (Jurnal Transformatika, 2020)
A Flooding is a disaster that often occurs in the Semarang area, especially on Jl. Raya Kaligawe. Flooding can occur due to the ineffectiveness of the pump work in a water impregnation pool. The impact of the floods is detrimental to students because with the flooding it can interfere with teaching and learning activities and studying student activities when on campus. At Sultan Agung Islamic University, Semarang has a water impregnation pool that is still manually controlled. By using Fuzzy Tsukamoto as artificial intelligence on Internet of Things technology, we can carry out intelligent control systems in water absorption pool pumps in realtime, so as to prevent and reduce human error that causes flooding. In principle, the Internet of Things works using a microcontroller, one of the microcontrollers that can be used, namely Wemos D1 mini. Wemos D1 mini is connected with an ultrasonic sensor to measure water level in a water infiltration pond, air temperature and air humidity sensor to detect rain.